Do Funds for More Teachers Improve Student Outcomes? - Nicolai T. Borgen; Lars J. Kirkebøen; Andreas Kotsadam; Oddbjørn Raaum (Center for Economic Studies and ifo Institute (CESifo), 2022)
We investigate the effects of a large-scale Norwegian reform that provided extra teachers to 166 lower secondary schools with relatively high student-teacher ratios and low average grades. We exploit these two margins using a regression discontinuity setup and find that the reform reduced the student-teacher ratio by around 10% (from a base level of 22 students per teacher), with no crowding out of other school resources or parental support. However, the reform did not improve test scores and longer-term academic outcomes, and we can reject even small positive effects. We do find that the reform improved the school environment from the students' perspective, but with the largest impact on aspects most weakly associated with better academic outcomes.
Keywords: J24; I20; 330; student-teacher-ratio; class size; test scores; non-cognitive skills; RDD